2019
DOI: 10.18203/2349-2902.isj20191262
|View full text |Cite
|
Sign up to set email alerts
|

Reamputation rates, morbidity and rehabilitation after lower limb amputations

Abstract: Background: This study attempted to document the indications for lower limb amputation (LLA) and its outcomes especially the wound healing problems, reamputations and subsequent use of prosthesis for mobilization in Indian population.Methods: This observational study included 92 patients over a period of 18 months. Indications, level of LLA, morbidity and reamputation rates after LLA were recorded. Stump status, wound healing and other morbidity was followed over period of one month. The use of prosthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In Chalya et al series [2] , 21% of them had wound infection of stump and 3.1% had wound dehiscence. In Umaru et al series, 28.3% had wound infection and 12.3% had wound dehiscence [22] . In Salawu et al series [25] , 10.7% had wound infection and 6.4% had flap necrosis after major amputation of extremities.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In Chalya et al series [2] , 21% of them had wound infection of stump and 3.1% had wound dehiscence. In Umaru et al series, 28.3% had wound infection and 12.3% had wound dehiscence [22] . In Salawu et al series [25] , 10.7% had wound infection and 6.4% had flap necrosis after major amputation of extremities.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies done by Jain et al found the major amputations in diabetic foot in major teaching hospitals to be between 16% to 20% [19,20] . Major amputation in diabetes patient is associated with significant social, economic and psychological impact on patients and their families along with decreased survival [21,22] . Further, major amputations have stump complications that increases morbidity, prolonged hospitalization and cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Once a patient has amputation being done for diabetic foot, it does not mean that he will be free from other problems arising from it. Many patients will have to use prosthesis in case they underwent major amputation (Vishwakarma, N. et al, 2019). Prosthesis related problems are well known.…”
Section: Category 5 -Subsequent Problemsmentioning
confidence: 99%